Rancang Bangun PLTS Off-grid Untuk Catu Daya Lampu Penerangan Kebun Buah Naga Desa Yosomulyo - Aldy Allan Ghozali; Lie Jasa; I Nyoman Satya Kumara (Study Program of Magister Electrical Engineering, 2025)
The sunlight intensity level requirement for dragon fruit plants is more than 90%, which is essential for the photosynthesis process and the morphological development of the plant. This plant is classified as long-day plant, meaning that it requires at least 12 hours or more of sunlight to reproduce. Dragon fruit farmers utilize artificial lighting as an alternative to sunlight to support the plant's biological processes at night. The energy source is conventional electricity from grid (PLN). The design of an off-grid PV system at the Yosomulyo dragon fruit farm is carried out to support the farm's daily electricity needs. The design begins with field observations to obtain geographic data of the farm, daily electrical load profile data with amperes, calculating the PV system capacity, determining PV system components, and testing the performance of the design with PVSyst simulation. The simulation results of the PLTS design are 70.9% with an inverter variation of 6500 W, solar modules of 550 Wp, batteries of 200 Ah 12 V at a system voltage of 48 VDC, and an autonomy day of 1.